Credit card use: do brand equity and materialism influence impulsive buying behavior? - Rodrigues, Luis Adriano; Oliveira, Marta Olivia Rovedder de (Revista de Administração da UFSM, 2021)
Purpose - This study aims to identify factors, such as materialism and brand equity, that can influence impulsive buying behavior associated with the use of a credit card. Design/methodology/approach - We adopted the survey method, collecting 384 structured face-to-face questionnaires, focusing on the footwear industry. We collected the data in the state of Rio Grande do Sul - Brazil, covering the seven mesoregions of the state. Confirmatory factor analysis, descriptive statistics, ANOVA, T test and Structural Equation Modeling (SEM) were used to analyze the data. Findings – In this study, we find that brand equity does not impact impulsive buying behavior, but the credit card positively impacts impulsive buying behavior. Research limitations/implications – The research was executed just in one province, so future research could be developed in other’s places and cultures Practical Implications – This study can help scholars and managers of footwear industry understand impulsive buying behavior of its consumers. Original value – This study shows the relationship between credit card use, materialism and impulsive buying behavior constructs.